2004
DOI: 10.4040/jkan.2004.34.7.1172
|View full text |Cite
|
Sign up to set email alerts
|

The Concept Analysis of Ego-integrity in the Elderly

Abstract: Ego-integrity is a concept having needs that should be treated in a specific way and it is possible to enrich the meaning and methods to manage ego-integrity in nursing interventions for promoting quality of life so that its application may have effects that have positive impacts on the elderly's well being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A prior study referred to the concept of ego integrity as the acceptance of past successes and failures, a perspective that considers one's past life as inevitable, appropriate, and meaningful (Hiel & Vansteenkiste, ; James & Zarrett, ; Ryff & Heincke, ; Torges, Stewart, & Duncan, ), while other studies also viewed ego integrity as encompassing satisfaction with one's present life and an acceptance of death in the future (Chang, Kong, Kim, & Choi, ; Chang et al , ). In this study, both of these concepts of ego integrity were found to be incorporated in the achievement of ego integrity by the nursing home residents and were verified via the nursing home staff members' subjective frame of reference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A prior study referred to the concept of ego integrity as the acceptance of past successes and failures, a perspective that considers one's past life as inevitable, appropriate, and meaningful (Hiel & Vansteenkiste, ; James & Zarrett, ; Ryff & Heincke, ; Torges, Stewart, & Duncan, ), while other studies also viewed ego integrity as encompassing satisfaction with one's present life and an acceptance of death in the future (Chang, Kong, Kim, & Choi, ; Chang et al , ). In this study, both of these concepts of ego integrity were found to be incorporated in the achievement of ego integrity by the nursing home residents and were verified via the nursing home staff members' subjective frame of reference.…”
Section: Discussionmentioning
confidence: 99%
“…Research that has examined ego integrity has suggested textbook theories, especially the work of Erikson. Preceding studies have been concerned with research on concept analysis (Chang, Kong, & Kim, ), the related variables (Afonso, Bueno, Loureire, & Pereira, ; Bauer, Schwab, & McAdams, ; Dezutter, Toussaint, & Leijssen, ), reminiscence (Bohlmeijer, Steunenberg, & Westerhof, ; Cappeliez, Rivarda, & Guindona, ; Chiang, Chu, Chang, & Chou, ; Gerben, Ernst, & Dean, ; Robitaille, Cappeliez, Coulombe, & Webster, ; Westerhof, Bohlmeijer, & Webster, ), and subjectivity (Chang et al , ). Most of these studies focus on the meaning of achieving ego integrity, measuring ego integrity by self‐report, and the connection between such self‐reports and the related variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, achieving ego-integrity is a multidimensional concept that includes independence, acceptance of life, psychological stability, harmony with others through empathy, overcoming difficulties, and spiritual well-being [32,33,34]. Therefore, when attempting to understand ego-integrity in seniors, it is important to achieve a comprehensive understanding of the physical, psychosocial, and spiritual factors that interact with the environment that the individual is placed in.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, Stern, McCants, and Pettine (1982) found that the positivity of the relation between changing life events and severity of illness was stronger for uncontrollable events (e.g., death of a spouse) than for controllable events (e.g., divorce). Ego integrity according to Chang et al. (2004) has been used frequently among health team members related to the care of the elderly and has specific meanings within the context of QoL.…”
Section: Past and Related Studies: Factors In Death Anxietymentioning
confidence: 99%